PERANCANGAN SISTEM INFORMASI PENCARIAN EVENT BERBASIS WEB - Gustino Dwiki Janarko, - (2018)
This research was conducted to make people in search of interesting event information around them. Searching for web-based events online can help people find interesting events for them. In this web also helps the community to know about the information activities in the event that held. This web event can also help Event Orgnizer or the public promote the event created by them. The method used in this research is Waterfall and WEB-based expected application with PHP programming language (Personal Home Page). The result of the research is by making a search system and web-based event making, all people can find interesting and useful events for them, and also promote event that will be held so that many people who attend or participate in the event activity